Long road to mercy [large type] - Baldacci, David (Baldacci, David. Atlee Pine series., 2018)
Eeny, meeny, miny, moe. Catch a tiger by its toe. It's seared into Atlee Pine's memory: the kidnapper's chilling rhyme as he chose between six-year-old Atlee and her twin sister, Mercy. Mercy was taken. Atlee was spared. She never saw Mercy again. Three decades after that terrifying night, Atlee Pine works for the FBI. She's the lone agent assigned to the Shattered Rock, Arizona resident agency, which is responsible for protecting the Grand Canyon. So when one of the Grand Canyon's mules is found stabbed to death at the bottom of the canyon-and its rider missing-Pine is called in to investigate. It soon seems clear the lost tourist had something more clandestine than sightseeing in mind. But just as Pine begins to put together clues pointing to a terrifying plot, she's abruptly called off the case. If she disobeys direct orders by continuing to search for the missing man, it will mean the end of her career. But unless Pine keeps working the case and discovers the truth, it could spell the very end of democracy in America as we know it...